Geraniol quality improvement on citronella oil as raw material for making anti-bacterial perfumes - Rihayat, Teuku; Suryani, Suryani; Hasanah, Uswatun; Nurhanifa, Nurhanifa; Siregar, J. P.; Jaafar, J.; Cionita, Tezara; Fitria, Fitria (Institute of Physics Publishing, 2020)
In this study, optimization was carried out to increase the levels of geraniol compounds present in citronella oil using vacuum distillation. Geraniol is a compound that has been legalized by IFRA (Fragrance International Research Association) as a scent compound, Geraniol has been studied in addition to having a pleasant fragrance, geraniol is also very effective in inhibiting bacterial growth. So geraniol is a reference to use it as formulated as a raw material for anti-bacterial products, but the levels of geraniol in citronella oil are still very low. This is what encourages the processing of fragrant citronella oil to be processed, by increasing geraniol levels using a vacuum distillation method, with variations in pressure: 8mmHg, 6mmHg, 4mmHg, 1mmHg during the operating time: 20 minutes; 40 minutes; 60 minutes and until Final boiling point. The samples were analysed using GC-MS (Gas Chromatography of Mass Spectrometry, FTIR (Fourier Transform Infra-Red Spectrophotometer), refractive index, and bacterial testing of research products. The results showed that higher temperature usage had an effect on increasing geraniol levels and showed that This vacuum distillation method is quite effective. Geraniol concentrations before and after isolation increased by 38%. namely from 20.32% to 57.39%. This shows that this method is quite effective in increasing geraniol concentrations in fragrant citronella oil. Analysis of FTIR shows 3365.78 cm-1 according to the hydroxyl polymer group (OH).